Social Identity and Aspiration - Double Jeopardy or Intersectionality? Evidence from Rural India - Sudipa Sarkar; Bhaskar Chakravorty; Clare Lyonette (Global Labor Organization (GLO), 2020)
This study investigates the relationship between individuals' social identity and their future aspirations in a developing country. We analyse primary survey data from participants of a large-scale skill-training programme that targets rural poor youths in India, focusing on two dimensions of individuals' identity: caste and gender. Our empirical findings suggest that training participants from the most socially disadvantaged groups - Scheduled Tribe (ST) and Scheduled Caste (SC) - have significantly lower income aspiration when compared to Other Backward Class (OBC) and Other Caste (OC) participants. Female participants also have significantly lower aspiration than their male counterparts. The aspiration gaps exist even after controlling for various background characteristics, including participants' pre-training personality traits and soft skills. Individual-level and household-level factors mediate some of the aspiration gaps based on caste and gender. We find evidence that for SC/ST female participants, the disadvantages on both caste and gender dimensions add up; this is reflected in their lower income aspiration levels, in comparison with all other groups. Thus, our results support the hypothesis of "double jeopardy" instead of "intersectionality" in this context.
Keywords: J15; J16; O12; Z13; 330; Social identity; Aspiration; Intersectionality; Gender; Caste; India